Relationship between fracturing and porogenesis in a carbonate reservoir: Example from the Middle Turonian Bireno Member in Jebel M'rhila, Central Tunisia. (September 2016) - Haj Ali, Hajer; Belghithi, Hanen; Ouali, Jamel Abdennaceur; Touir, Jamel
Abstract: The aim of the present work is to study the Middle Turonian carbonate Bireno Member in Jebel M'rhila area (Central Tunisia). This member mainly consists of dolostones. The sampling of the dolomitic rocks was carried out on both sides of the several fractures affecting the Bireno Member. We also measured the directions and dips of the fractures. The Studied dolomites basically consist of subhedral to euhedral dolospar. The porosity associated to the dolomites show a gradual variation both laterally and vertically. In fact, porosity increases respectively, laterally while going toward the fractures and vertically from the bottom to the top of the dolomitic member. The mineralogical and geochemical analyses of dolomite, carried out respectively by X-Ray Diffraction and Atomic Absorption, show that the studied dolomites broadly range from a sub-stoechiometric dolomite (48% CaCO3 ) far from the fractures to a dolomitic calcite (84% CaCO3 ) near the fractures. In the same way, the MgCO3 contents vary from 35% to 11%. Such high contents in Ca against low contents in Mg could probably related to the dilution of the dolomitizing marine waters by meteoric waters which would have been introduced within the platform during the Middle Turonian sea-level fall and the subsequent subaerial exposure of the Bireno platform. The Sr and Na contents (respectively, 4 ppm and 15 ppm in average) are rather low and they gradually decrease while approaching the fractures. Such a gradual decrease in Sr and Na concentrations may be the result of salinity lowering caused by the meteoric waters that would have circulated through the existing fractures networks. The previous analyses were supplemented by the SEM examination of the dolomite and the measurement of porosity and permeability. The SEM allowed us to identify the dolomite petrographic phases and the associated diagenetic products (solution, cementing, dedolomitization.), whereas the porosity and permeability evaluation highlights the relationship between fracturing and the reservoir potentiality of dolomites and the dolomitization process. Although the porosity in dolomites is not important enough, its gradual lateral variation with the distance from the fractures reflects the role of the latter in the porogenesis. The field observation and the results of the petrographic and petrophysical analysis show that the fractures must have played a substantial role in conducting the meteoric waters from the emerged platform surface to its base and laterally, resulting in a cementing dolomitization and a solution-related porogenesis. Therefore, it seems that if the dolomitic Bireno Member is rather a good potential reservoir due to the associated fractures networks. Highlights: The Studied dolomites primarily consist of subhedral to euhedral dolosparite. The porosity is increasing laterally while going toward the fractures and vertically from the base to the top of the dolomitic member, which shows the role of the fracturing in the porogenesis. The mineralogical and geochemical analyses of dolomite carried out respectively by X-ray diffraction and atomic absorption show that the studied dolomites broadly range from a sub-stoechiometric dolomite (48%) far from the fractures to a dolomitic calcite (84%) near the fractures. Therefore, it seems that if the Bireno dolomitic member is rather a good reservoir, it is thanks to the associated networks of fractures.